MOLECULAR DOCKING STUDIES OF ISATIN-LINKED CHALCONE DERIVATIVES AS PANKASSOCIATED NEURODEGENERATIVE DRUG CANDIDATES AND THEIR ADMET PREDICTION - MARAPATLA SHINY; GIRIJA SASTRY VEDULA; KUSUME SIREESHA; GARA SUREKHA; CHALLA VIJAYA SRUTHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Molecular docking studies were carried out on fifteen novel Isatin-linked chalcone derivatives to evaluate their potential as drug candidates for PanK-associated neurodegeneration. Methods: The compounds were computationally analyzed using Molegro Virtual Docker, Autodocktools, and AU docker against the Pantothenate kinase protein (PDB ID: 6B3V). Results: The molecular docking analysis revealed that the synthesized chalcones exhibited significant binding affinities with dock scores ranging from −8.4 to −9.1 kcal/mol, surpassing the standard Pantazine derivative PZ-2891 (−7.0 kcal/mol). Compound 14 demonstrated superior binding affinity (−9.1 kcal/mol) through key interactions with SER-175, PHE-306, ASN-305, and THR-11 residues. The binding modes were validated through consensus scoring and root-mean-square deviation analysis. ADMET predictions using SwissADME indicated favorable drug-like properties for the compounds, including blood-brain barrier permeability and acceptable bioavailability scores. Conclusion: The computational analysis revealed that 80% of the compounds exhibited interactions with serine residues, similar to the standard drug’s binding pattern. Structure-activity relationship analysis identified key pharmacophoric features contributing to enhanced binding affinity, particularly the presence of specific substituents on the chalcone scaffold.